PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN INTELEKTUAL TERHADAP SIKAP ETIS AUDITOR PEMERINTAH KABUPATEN SE MADURA - Nurul Fitriani; Suryani Dwi Kuswardhini; Mohammad Herli (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Ethical attitude is attitude and behavior which accordance with social normsgenerally accepted in connection with the actions that beneficial and harmful. This studyexamines the affect of Sprititual Quotient and Intellectual Quotient toward EthicalAttitude Government auditors in Madura. This study conduced to Government auditorswhich worked in MaduraInspectorates by surfeited sampling method and obtained 78sample auditors. Examination technique that used in this study is linear regressionexamination. The result indicates that Sprititual Quotient and Intellectual Quotientsimultaneously have affect to Ethical attitude with signification 0,000. Partially,Sprititual Quotient has significance affect to Ethical attitude with signification 0,020, andIntellectual Quotient has significance affect to Ethical attitude with signification 0,000.